A Yb:KGW dual-crystal regenerative amplifier. (2020) - He, Huijun; Yu, Jun; Zhu, Wentao; Guo, Xiaoyang; Zhou, Cangtao; Ruan, Shuangchen
Abstract: This study develops a Yb:KGW dual-crystal based regenerative amplifier. The thermal lensing and gain-narrowing effects are compensated by the dual-crystal configuration. Sub-nanojoule pulses are amplified to 1.5 mJ with 9 nm spectral bandwidth and 1 kHz repetition rate using chirped pulse amplification technology. Consequently, 1.2 mJ pulses with a pulse duration of 227 fs are obtained after compression. Thanks to the cavity design, the output laser was a near diffraction limited beam with M 2 around 1.1. The amplifier has the potential to boost energy above 2 mJ after compression and act as a front end for a future kilohertz terawatt-class diode-pumped Yb:KGW laser system.